Instrumentation of Psychospiritual Scale for Malaysian Drug Rehabilitation Centres - Amin Al Haadi Shafie; Nurul Ashikin Binti Ahmat Miskam; Mohd Rushdan Mohd Jailani; Muhammad Khairi Mahyuddin; Hishamuddin Abdul Wahab (Human Resource Management Academic Research Society, 2024)
Indexed by ERA